Pengaruh Pengetahuan, Kemampuan, Pengalaman Kerja Terhadap Kinerja SDM Pada Industri Batik Gedog (Studi Kasus Industri Batik Budi Karya H. M. Sholeh Kerek, Kabupaten Tuban) - Heri Ahmad Suyudi; Eka Farida; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis research was conducted to determine the effect of knowledge, ability and work experience on performance in the batik industry of Gedog H.M Sholeh Kerek Kab. Tuban. This research uses explanatory research and quantitative approach. Non Probability Sampling technique to take samples, which is a sampling method when all members of the population are used as a sample of 40. To solve the problem in this study, use validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. This study uses multiple linear analysis with the help of SPSS 25. 0 The results of this study are the variables Knowledge, Ability and Experience simultaneously and partially affect Employee Performance in the Batik Industry H.M Sholeh Keywords: Employee Performance, Knowledge, Ability, and Experience